مصطلح الشعر في التراث النقدي لأحمد زكي أبي شادي - بوعلاق, مسعودي, سلسبيل جيهان (University of El-oued, 2022)
هدفت هذه الدراسة تحديدا الى مفهوم الشعر انطلاقا من موقع فكري محدد الا وهو الشعر عند احد كبار الشعراء أحمد زكي أبي شادي، وقد توزع على فصلين اساسيين: الفصل الاول احتوى على تعريف الشعر عند احمد زكي ابي شادي والذي قام بدوره ببناء تصور جديد للشعر قائما على مرجعية غربية، كما ذكرنا مجموعة العناصر الشعرية التي لم يتحدث عنها سابقا كالعاطفة، الخيال، التأمل. ثم انتقلنا الى وظيفة الشعر والتي بدورها تنوعت وتعددت، ثم الى محاسن الشعر وعيوبه، اما الفصل الثاني فقد قمنا بتحديد بعض المصطلحات المتفرعة عن مصطلح الشعر اذ أن أبي شادي توسع في شعره من خلال المصطلحات الفرعية المتمثلة في الضمائم الوصفية والضمائم الاضافية. وفي الاخير ختمنا بحثنا بأهم النتائج. This study aimed specifically at the concept of poetry based on a specific intellectual site, which is poetry according to one of the great poets, Ahmed Zaki Abi Shadi. Western reference, as we mentioned a group of poetic elements that he did not talk about previously, such as emotion, imagination, meditation. Then we moved to the function of poetry, which in turn varied and varied, and then to the advantages and disadvantages of poetry. As for the second chapter, we have defined some terms branching from the term poetry, as Abi Shadi expanded on his poetry through the sub-terms represented in descriptive and additional enclosures. Finally, we concluded our research with the most important results.
Keywords: مفهوم الشعر، التراث النقدي، أحمد زكي أبي شادي، مصطلحات الشعر; concept of poetry, critical heritage, Ahmed Zaki Abi Shadi, terminology of poetry.